2005
DOI: 10.1002/gj.1018
|View full text |Cite
|
Sign up to set email alerts
|

The pre‐radial history of echinoderms

Abstract: Gene sequence data now identify a robust phylogeny of deuterostomes and provide a framework within which the evolution of echinoderms can be interpreted. The topology of the molecular tree makes a number of important predictions about the morphological characters of the earliest echinoderm at its split from hemichordates: it possessed gill slits (but not a notochord), had a bilaterally symmetrical body plan in the adult and, less certainly, underwent torsion during development. Carpoids, a highly contentious g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(164 citation statements)
references
References 56 publications
(117 reference statements)
9
152
0
3
Order By: Relevance
“…However, echinoderms have a mineralized skeleton with a very distinctive morphology termed stereom that is underpinned by a unique family of genes 42 . It is the first synapomorphy of echinoderms that can be recognized 17 and the evolution of a mesoskeleton composed of stereom must thus predate diversification of the clade into bilateral, asymmetrical, spiral-radiate and pentaradiate body plans. Because of its distinctive microstructure, even isolated plates of echinoderms are easily recognizable in petrological thin sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, echinoderms have a mineralized skeleton with a very distinctive morphology termed stereom that is underpinned by a unique family of genes 42 . It is the first synapomorphy of echinoderms that can be recognized 17 and the evolution of a mesoskeleton composed of stereom must thus predate diversification of the clade into bilateral, asymmetrical, spiral-radiate and pentaradiate body plans. Because of its distinctive microstructure, even isolated plates of echinoderms are easily recognizable in petrological thin sections.…”
Section: Discussionmentioning
confidence: 99%
“…570 Ma, implying some 50 my of missing echinoderm fossil record. Furthermore, some argue from comparative morphological grounds that peculiar asymmetric to bilaterally symmetric clades of echinoderm represent the primitive echinoderm body plan, even though they appear in the fossil record somewhat later than radiate forms [16][17][18][19] .…”
mentioning
confidence: 99%
“…4 The interrelationships of living and fossil echinoderms within the context of Deuterostomia. Primarily based upon Smith (2005Smith ( , 2008 and Bourlat et al (2008) indicate a position higher in a tree are absent because they were never present or merely because they rotted away (Donoghue and Purnell 2009). Thus, various fossil organisms, such as the yunnanozoans (including Haikouella), have been interpreted as primitive deuterostomes (Shu et al 2003b), primitive ambulacrarians (Shu et al 2004), or as primitive chordates (Shu et al 2004) because they seem to possess those few necessary characteristics, such as gill slits.…”
Section: The Origins Of Other Deuterostome Phyla and The Limitations mentioning
confidence: 99%
“…The hemichordate gill slits and bars are located dorsally, opposite to the ventral mouth, while in the cephalochordates and vertebrates, the gill slits and bars are located ventrally (Swalla 2007). Gill openings are also dorsal in stemgroup echinoderms (Smith 2005). Recent results have shown that the dorsal side of a juvenile hemichordate is determined by a stripe of expression of bone morphogenetic protein (BMP) gene expressed dorsally, and its ventral side by an expression stripe of BMP antagonists, including chordin , just as has been reported for the arthropods (Sasai & De Robertis 1997).…”
Section: Conserved Gene Network Pattern Deuterostome Axes and Germ Lmentioning
confidence: 78%